Stoma care is our affair for the senior citizens everywhere - M. Coyle; M. Dixon (AOSIS, 1983)
The first reported colostomy was in 1776 and it was a caecostomy, or opening into the caecum. This was the first attempt to surgically help the problem of an imperforate anus. The first stomatherapist was a patient in the Cleveland Clinic, Ohio, U.S.A. Now there are 22 countries in the world with qualified stomatherapists. Stomatherapy was founded in South Africa in 1958 and in England in 1967.